Crip authorship : disability as method - Mills, Mara; Sanchez, Rebecca, 1984- (New York University Press, 2023)
"An expansive volume presenting crip approaches to writing, research, and publishing Crip Authorship: Disability as Method is a comprehensive volume presenting the multidisciplinary methods brought into being by disability studies and activism. Mara Mills and Rebecca Sanchez have convened leading scholars, artists, and activists to explore how disability shapes authorship, transforming cultural production, aesthetics, and media. Starting from the premise that disability is plural and authorship is an ongoing project, this collection of thirty-five compact essays asks how knowledge about disability is produced and shared in disability studies. Crip authorship takes place within and beyond the commodity version of authorship, in books, on social media, and in creative works that will never be published. Crip authorship celebrates people, experiences, and methods that have been obscured; it also involves protest and dismantling. It can mean innovating around accessibility or attending to the false starts, dead ends, and failures resulting from mis-fit and oppression. The chapters draw on the expertise of international researchers and activists in the humanities, social sciences, education, arts, and design. Across five sections-Writing, Research, Genre/Form, Publishing, Media-contributors consider disability as method for creative work: practices of writing and other forms of composition; research methods and collaboration; crip aesthetics; media formats and hacks; and the capital, access, legal standing, and care networks required to publish. Designed to be accessible and engaging for students, Crip Authorship also provides theoretically sophisticated arguments in a condensed form that will make the text a key resource for disability studies scholars."--